2018
DOI: 10.1155/2018/4821821
|View full text |Cite
|
Sign up to set email alerts
|

Regulation Effect of a Chinese Herbal Formula on Flora and Mucosal Immune Secretory Immunoglobulin A in Rats

Abstract: Flora and mucosal immunity are considered to be the barrier, which is associated with multiple respiratory diseases, including recurrent respiratory tract infection (RRTI). Fei-Xi-Tiao-Zhi-Fang (FTF) is a traditional Chinese herbal formula used in the treatment of RRTI. However, the mechanism is little known. This study aims to identify the function of FTF in flora and mucosal immune secretory immunoglobulin A (sIgA) in the model of RRTI rats. The samples of intestine and lung were collected to detect sIgA, sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Furthermore, increased intestinal sIgA secretion was reported to result from the influence of consuming phenolic- and triterpenoid-rich herbs or medicinal fungus. Liu et al. (2018) showed that Chinese herbal formula Fei-Xi-Tiao-Zhi-Fang significantly upregulated intestinal sIgA concentration, while Cordyceps militaris also showed to increase the ileal sIgA level in E. coli (ATCC 25922)-infected mice ( Zhang et al., 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, increased intestinal sIgA secretion was reported to result from the influence of consuming phenolic- and triterpenoid-rich herbs or medicinal fungus. Liu et al. (2018) showed that Chinese herbal formula Fei-Xi-Tiao-Zhi-Fang significantly upregulated intestinal sIgA concentration, while Cordyceps militaris also showed to increase the ileal sIgA level in E. coli (ATCC 25922)-infected mice ( Zhang et al., 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…At present, there is no common criterion to judge the balance of lung bacteria. Previously, we used TCM to interfere with flora and immune disorder in model rats, and found that the balance in lung and intestine bacteria of model rats was improved [57].…”
Section: Discussionmentioning
confidence: 99%
“…Gut bacteria play an important role in the digestion and absorption of nutrients in food and are considered as therapeutic targets of many diseases and drugs (30,31). It has become a hot research method in modern pharmacology to study the molecular mechanisms of drug treating diseases by focusing on gut bacteria (20,21). In order to further verify the potential mechanisms of VK2 for salt-sensitive hypertension, we supplemented VK2 to intervene high-salt induced mice, and detected the characteristics of gut bacteria by 16S rRNA analysis.…”
Section: Discussionmentioning
confidence: 99%